BRICS carbon emissions: Asymmetric impact of energy mix, financial development, and digitalization - Dhyani Mehta; Mohd Asif Shah (Sustainable Environment)
The group of nations which includes Brazil, Russia, India, China, and South Africa (BRICS) need to address rising energy demand, reduce carbon emissions, and sustain economic growth, necessitating a strategy that integrates environmental sustainability with economic development. The current study delves into the profound impact of energy mix, financial development, digitalization, and national income on carbon emissions in BRICS countries. The study uses a nonlinear panel quantile regression model utilizing panel data spanning from 2000 to 2023, by estimating the asymmetric impact of energy mix, financial development, and digitalization on carbon emissions of BRICS countries. The estimates assert that a higher energy mix ratio, favoring renewable sources for energy generation, serves as a potent catalyst in mitigating carbon emissions. Moreover, the study highlights the pivotal role of financial development in curbing carbon emissions by fostering investment in green energy and encouraging sustainable energy consumption. Furthermore, the study underscores the transformative effect of digitalization in BRICS countries, leading to a reduction in carbon emissions. This exemplifies how BRICS countries have strategically leveraged financial development and digitalization to significantly reduce carbon emissions. However, the study also prompts policymakers to address the challenges posed by increased energy consumption from non-renewable sources amid developmental activities. By providing fresh evidence on the impact of the energy mix, financial development, and digitalization on carbon emissions, this study augments the existing literature and underscores the imperative for concerted action in addressing environmental concerns.